Managerial cognitive capabilities, organizational capacity for change, and performance: The moderating effect of social capital - Beta Embriyono Adna; Badri Munir Sukoco (Cogent Business & Management, 2020)
The aim of this study is to analyze the role of organizational capacity for change as a mediator between managerial cognitive capabilities with organizational performance. Further, we investigate the moderating role of social capital on the influence of organizational capacity for change on organizational performance. We surveyed middle managers and their immediate followers (supervisor level) in the Directorate General of State Asset (DGSA), Ministry of Finance, Republic of Indonesia. Overall, 313 middle managers and their followers participated in this study. The results demonstrate that organizational capacity for change mediate the influence of managerial cognitive capabilities on organizational performance. In addition, there is no significant moderating effect of social capital on the influence of organizational capacity for change on organizational performance. Theoretical and managerial implications are further presented in this study.
Keywords: 650; Managerial cognitive capabilities; organizational capacity for change; organizational performance; social capital; public organization; Indonesia